Instrumentalism in the Law of Trusts – The Disturbing Case of the Constructive Trust Upon an Express Trust - Rickett, C EF (Victoria University of Wellington Law Review, 2016)
New Zealand courts have begun to use the device of imposing a constructive trust over assets already held on trust under an express trust. This device raises a number of important issues about whether a doctrinally damaging analysis should be used to achieve what are clearly instrumental designs usually termed justice or fairness. This article examines the issues in depth and argues strongly that the device of a constructive trust on an express trust is illegitimate.